Influence of a microalloying addition of Ag on the precipitation kinetics of an Al-Cu-Mg alloy with high Mg:Cu ratio - Macchi, Carlos Eugenio (2015)
Effects of microalloying with Ag on the precipitation process in an Al-Cu-Mg alloy with high Mg:Cu ratio have been investigated during artificial ageing of the ternary and quaternary compositions Al-1.5 wt.%Cu-4 wt.%Mg(-0.5 wt.%Ag) at 175 °C, combining transmission electron microscopy and positron lifetime spectroscopy. In addition, coincidence Doppler broadening of the positron-electron annihilation radiation was used to provide information about the chemical environment surrounding vacancy-like defects. The results obtained for the silver-free alloy indicate that, immediately after quenching from the solution treatment temperature, vacancy v-Cu-Mg clusters are formed in the supersaturated solid solution. During the early stages of ageing these clusters become richer in Cu and Mg and laths of the S phase (Al2CuMg) nucleate preferentially on dislocation lines. Continued ageing led to gradual precipitation of an equi-axed phase in the matrix between the S phase laths which is believed to be the cubic Z phase thought previously to form only if silver is present. For the silver-containing Al-Cu-Mg alloy, v-Cu-Mg-Ag aggregates also form immediately after quenching and the solute transport mechanisms are the same. However, precipitation of the S phase is suppressed during ageing and the silver addition promotes accelerated formation of a finer dispersion of smaller equi-axed Z phase precipitates. For both alloys, no evidence was found that the Z phase is preceded by any pre-precipitate or GP zones. Combination of coincidence Doppler broadening and microanalysis results revealed the Z phase to have a Mg:Cu ratio of 2 which indicates that it differs from the well known T phase (Al6CuMg4) which the equilibrium phase diagram indicates should form in Al-Cu-Mg alloys with high Mg:Cu ratios. Additional ageing experiments at 240 °C showed that neither the Z phase or T phase are formed in the ternary alloy, but only precipitates of the S phase, while in the quaternary alloy the S phase is strongly suppressed and mainly Z phase precipitates are formed.